Nursing Care in Schizophrenic Clients (Delusion) in Hospital Service Management: A Case Study - Eriyono Budi Wijoyo; Mustikasari Mustikasari (Universitas Muhammadiyah Tangerang, 2020)
Introduction: care for mental patients needs to be continuous and collaboration between health workers and the client's family is needed. This collaboration can be done by carrying out one of the complementary training activities to extend the recurrence time and prepare the client to return to the community. Objective: to find out schizophrenia nursing care in a hospital. Method: The process of writing this scientific article uses a case study approach with a descriptive method drawn from the life and personal experience of the author. To collect data in the form of articles, the author uses several databases, namely Science Direct and Google Search. The author also uses several search keywords such as